Analisis Penerapan Akuntansi Lingkungan Terhadap Pengendalian Biaya Operasional Pengelolaan Limbah pada Rumah Sakit Karya Husada - Riska Febriyanti; Devi Astriani; Ade Trisyanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to find out how environmental accounting is applied to control operational costs for waste management at Karya Husada Hospital. This research was conducted using qualitative methods. Data sources use primary data and secondary data. The data analysis technique used is descriptive qualitative using the Miles and Huberman model. The results of this research show that Karya Husada Hospital has managed its waste well, this is proven by the absence of problems or complaints from the surrounding community regarding waste at the hospital. Karya Husada Hospital has implemented environmental accounting and carried out the process of Recognizing, Measuring, Recording, Presenting, and also Disclosure of environmental related costs. Karya Husada Hospital does not have a specific environmental cost report. Controlling operational costs for waste management at Karya Husada Hospital has not been effective, where there has been a deviation from realized costs exceeding previously budgeted costs. This deviation occurred because the amount of medical and domestic waste increased along with the increase in patient and family visits at Karya Husada Hospital.